Corrosive Esophagitis and Gastritis Induced by Glutaraldehyde Ingestion - Donghwan Jun; Hye-Jin Kim; Hyun Suk Lee; Hong Jip Yoon; Jae Yong Park; Beom Jin Kim; Jae Gyu Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Corrosive esophagitis and gastritis are characterized by caustic damage due to ingestion of chemical agents. Caustic agents cause tissue destruction through liquefaction or coagulation reactions. Here, we report a case of corrosive esophagitis and gastritis caused by accidental ingestion of glutaraldehyde in Korea. A 62-year-old man presented to the emergency department 8 hours after ingesting glutaraldehyde, which is widely used for the prevention of foot-and-mouth disease in pigs. Urgent endoscopic examination revealed severely damaged mucosae of the esophagus and stomach. With conservative treatment, the patient’s condition was improved, and he was discharged on the 35th day of admission.